Effect of a surgical sponge counting stand on counting discrepancies, time efficiency, and operating room staff satisfaction: A quality improvement study - Naeimeh Eftekhari; Akram Aarabi; Aygineh Hairabedian (Nursing and Midwifery Studies, 2025)
Background: Retained surgical items (RSIs), particularly surgical sponges, represent a significant and preventable error in surgical practice, leading to severe patient complications and legal repercussions for healthcare providers. Despite the adoption of various counting protocols and technologies, discrepancies in sponge counts persist, particularly in resource-limited settings where high-cost technologies are not feasible.Objectives: This study aimed to evaluate the effect of a new, cost-effective surgical sponge counting stand on reducing counting discrepancies, decreasing the time required for sponge counts, and enhancing staff satisfaction with the counting process at a large general hospital in Isfahan.Methods: This interventional pre-test and post-test single-group study was conducted in 2023, involving 44 operating room staff members participating in 37 open abdominal, pelvic, and thoracic surgeries. Data on counting discrepancies, time taken for counts, and staff satisfaction were collected before and after the implementation of the new counting stand. Data analysis was performed using SPSS version 16, employing descriptive statistics, paired t-tests, and Wilcoxon tests with a significance level set at 0.05.Results: The surgical sponge counting stand significantly reduced the time required for sponge counting during tissue closure (P<0.001) and skin closure (P<0.001), and significantly decreased overall counting discrepancies (P=0.01). Operating room staff satisfaction with the counting process significantly improved post-intervention (P<0.001).Conclusion: The implementation of the new surgical sponge counting stand significantly improved both the accuracy and efficiency of the sponge counting process while also enhancing operating room staff satisfaction. Given its cost-effectiveness, this tool presents a viable solution for improving surgical safety, particularly in settings where high-cost technologies are impractical.